Decentralized Peer Review and e-Assessment in Hybrid Learning: Blockchain as a Tool for Equitable Feedback Mechanisms - Sevda Kara; Murat Arslan; Zeynep Toprak (Journal Emerging Technologies in Education, 2025)
Background. The integrity and equity of assessment in hybrid learning environments have been increasingly challenged by issues of transparency, bias, and centralized control. Traditional peer review systems often lack traceability and accountability, leading to concerns about the fairness and credibility of formative feedback. Purpose. This study explores the application of blockchain technology as a decentralized infrastructure for peer review and e-assessment in hybrid learning contexts. The research aims to evaluate how blockchain-based systems can enhance feedback transparency, reviewer accountability, and student trust in digital assessment processes. Method. Employing a design-based research methodology, a prototype blockchain-enabled peer assessment platform was developed and tested with 92 university students across two hybrid courses. Quantitative and qualitative data were collected through platform analytics, student surveys, and focus group discussions. Results. The results demonstrate that blockchain-based systems can serve not only as secure ledgers but also as ethical architectures for equitable formative assessment Conclusion. The study concludes that blockchain offers a viable mechanism for building equitable, transparent, and tamper-resistant assessment systems in hybrid learning. The research contributes to the growing field of educational technology by introducing a scalable model for decentralized e-assessment.